Numerical Simulation of Falling Liquid Film Flow on a Vertical Plane by Two-Phase Lattice Boltzmann Method. (17th January 2013) - Hantsch, Andreas; Gross, Ulrich
Abstract : Falling liquid film flow is widely used in many processes. Supplementary to experimental studies, Navier-Stokes-based models have been employed for describing film flow phenomena. These models are often disadvantageous since they are either strongly limited in their generality or need enormous computational resources. In this investigation, a new approach is proposed for modelling flow by lattice Boltzmann methods. Therefore, the well-known Shan-Chen model (Shan and Chen, 1993) has been employed to an isothermal falling liquid film. The validity of the implementation has been checked against some single-phase and two-phase reference cases. Test series have been conducted for three different Reynolds numbers without external disturbances and for one Reynolds number with sinusoidally pulsating inlet velocity. The computational results show that lattice Boltzmann methods are capable to model falling liquid film flow and that the flow morphology is in qualitatively good agreement with other numerical and experimental works.